Effects of Nisin and Nitrite on Some of The Chemical Characteristics of “Sucuk”-A Dry Fermented Turkish Sausage - Kurt, Sukru; Zorba, Omer (Asian Journal of Chemistry, 2010)
The effects of nitrite (0, 100 and 200 mg kg-1) and nisin (0, 250 and 500 mg kg-1) on pH, moisture, lipolysis, peroxide, proteolysis and residual nitrite values of Sucuk-a dry fermented Turkish Sausage were investigated by utilizing central composite design of response surface methodology. While additional nitrite levels linearly decreased peroxide values (p < 0.05), they increased residual nitrite values significantly (p < 0.01). Residual nitrite levels were found below 6 ppm at the end of the ripening period. The effects of nitrite and nisin were not found to be significant (p > 0.05) on pH, moisture, lipolysis and proteolysis values for the sucuk.